ANALISIS SIFAT FISIKA, KIMIA DAN BIOLOGI AIR SUMUR BOR DI LINGKUNGAN UNIVERSITAS TEUKU UMAR - Muhammad Arif Nasution; T Amarullah; Muhammad Agam Thahir (JURNAL PERIKANAN TROPIS, 2020)
The aim of this study is to measure the physical properties (Temperature, TDS, Turbidity), chemistry (pH, DO, BOD, Phosphate, Nitrate) and biology (Fecal coliform) of groundwater water quality in the Teuku Umar University environment. This research was carried out for 4 months, i.e. water sampling was carried out in August, physical, chemical and biological properties were measured in September to October and data analysis was carried out in November. Sampling at 11 stations. The results of temperature measurements are 26-290C, with an average value of 27.50; TDS between 122 - 410 mg / l with an average of 234.5 mg / l; turbidity ranged from 3.89-85.55 NTU, with an average value of 17.3 NTU; Water pH ranged from 6.65 to 6.7.65, with an average value of 7.1; DO ranges between 1.2 - 2.5 mg / l average value of 1.5 mg / l; BOD5 ranges from 0.7-2.71 mg / l, with an average of 1.7 mg / l; Phosphate ranges from 0.19 - 2.08 mg / l with an average value of 1.1 mg / l; Nitrates range from 0.2 - 0.6 mg / l with an average value of 0.5 mg / l; Fecal coliform ranges from 0 - 90 ml / 100 ml with an average value of 24 mg / l.